2009
DOI: 10.1002/jpln.200800093
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry nutrient management for silk production in Hubei Province of China

Abstract: The silk industry is important for south China's rural economy. Leaves of mulberry (Morus spp.) are used for silkworm production. Hubei province is one of the main silk‐producing provinces in China. The objectives of this research were to survey the fertilization practices in the mulberry‐producing regions in the province and to determine the best nutrition‐management practice for mulberry plantations. A survey and a series of field experiments with N, P, K, and micronutrients were conducted from 2001 to 2002.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 3 publications
1
9
0
1
Order By: Relevance
“…Subsequently, the rise in the concentration of monovalent cations (i.e., K + ) would displace some of the divalent ions from the carboxylate salts and increase electrostatic screening around anionic groups, reducing the amount of interchain bridging and lowering the viscosity. If correct, this mechanism represents a chemically simple method by which the silkworm can alter the viscosity of the feedstock, by controlling the ion concentration in the gland via its own ion‐transport proteins, using species abundant in its foodstuff (mulberry leaves) …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the rise in the concentration of monovalent cations (i.e., K + ) would displace some of the divalent ions from the carboxylate salts and increase electrostatic screening around anionic groups, reducing the amount of interchain bridging and lowering the viscosity. If correct, this mechanism represents a chemically simple method by which the silkworm can alter the viscosity of the feedstock, by controlling the ion concentration in the gland via its own ion‐transport proteins, using species abundant in its foodstuff (mulberry leaves) …”
Section: Discussionmentioning
confidence: 99%
“…In the land south of the Yangtze River, farmers need to add K fertilizer for high yields [31]. However, the concentration of available K (125 mg kg -1 ) in urban soil of this region was found to be moderate, slightly higher than the rural average of 79.3 mg kg -1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the leaf yields of mulberry in Hubei Province which is one of the main silk-producing regions in China are about half lower than those in other leading silk-producing provinces, such as Guangxi, Guangdong and Zhejiang [15]. A previous survey suggested that fertilizer application has become an important factor that limits leaf yield and quality in Hubei province [15]. In order to obtain large quantities of leaves, farmers often use inorganic fertilizers, particularly nitrogen fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain large quantities of leaves, farmers often use inorganic fertilizers, particularly nitrogen fertilizers. Currently, nitrogen fertilizers are applied to mulberry plantations at the high rate of 454 kg N ha –1 y –1 in Hubei Province [15]. However, few studies have investigated the effects of this high input level on the changes in soil microbial community composition and diversity [16–17].…”
Section: Introductionmentioning
confidence: 99%